Learning Geometry of Flat Buildings Based on Batak Traditional Houses to Improve Numeracy Skills in Elementary Schools - Lubis, Jumaita Nopriani; Agustini, Rini; Pelangi, Herman; Dalimunthe, Rahmah Yasrah; Sari, Yulita (Institut Agama Islam Daruttaqwa Gresik, 2025)
Numeracy is a fundamental skill in elementary mathematics education, yet conventional teaching methods often fail to connect abstract concepts with students’ lived experiences. This study was motivated by the need for more contextual and meaningful learning models, particularly through the integration of local cultural heritage. The research aimed to: (1) determine whether there is a significant difference in numeracy skills between fourth-grade students at SD Swasta Muhammadiyah 2 Padangsidimpuan who received geometry instruction based on Rumah Adat Batak (Rumah Bolon) and those who received conventional instruction, and (2) examine the improvement in students’ numeracy skills after participating in the culturally integrated learning. A quasi-experimental method was employed using a pretest-posttest control group design. The sample consisted of 64 students divided into an experimental class and a control class. A multiple-choice numeracy test was used as the research instrument. Data were analyzed using a t-test and N-Gain calculation. The results revealed a significant difference between the two groups (t = 2.138; p = 0.036 < 0.05), with the experimental group achieving higher scores. The average N-Gain score of 0.42 indicated a moderate improvement in numeracy skills. These findings suggest that geometry instruction incorporating Rumah Bolon effectively enhances students’ numeracy in a more meaningful way. The study implies that integrating local cultural contexts into mathematics curricula can strengthen conceptual understanding and support national numeracy goals. This approach offers a promising pathway for culturally responsive pedagogy in Indonesian elementary education.